Association of life's essential 8 and genetic predisposition with the risk of osteoarthritis: a prospective cohort study - Du, Changyu; Zhou, Tingting; Ji, Xiang; Tang, Xiaofu; Yang, Honghao; Ma, Zheng; Kuang, Mingjie; Chen, Liangkai; Li, Xiaofeng; Wang, Hongfei; Yang, Chengrui; Li, Xiaoming; et al. (Frontiers in Nutrition, 2025)
BackgroundOsteoarthritis (OA) is a prevalent joint disorder with significant health and economic impacts. While individual cardiovascular health (CVH) factors have been linked to OA, a comprehensive understanding of how overall cardiovascular health influences OA risk is lacking. Life's Essential 8 (LE8) offers a holistic measure incorporating physical activity, body mass index, diet, sleep, blood pressure, blood sugar, lipids, and nicotine exposure. The inclusion of LE8 in OA research is crucial to better understand the broader cardiovascular health-OA association.MethodsThe present study was conducted using data from the UK Biobank, which initially included more than 500,000 participants. After applying exclusion criteria, a total of 242,278 participants without hip and/or knee OA at baseline were included in the final analyses. Genetic risk scores (GRSs) for hip, knee, and hip/knee OA were derived from 70, 83, and 87 single-nucleotide polymorphisms, respectively. Restricted cubic splines (RCS) were utilized to explore the potential non-linear associations of GRSs with the risks of OA. Cox proportional hazards models were applied to assess the associations between LE8, GRSs, and the risk of OA. Both combined effect and interaction analyses were conducted to evaluate how LE8 and GRSs jointly influence OA risk.ResultsDuring a median follow-up period of 12.12 years, 18,767 participants developed hip and/or knee OA. LE8 was found to be negatively associated with the risks of hip, knee, and hip/knee OA. CVH, as measured by LE8 scores, was categorized into three groups based on the following boundary values: high CVH (80–100 points), moderate CVH (50–79 points), and low CVH (0–49 points). Compared to the participants with low CVH, the HRs (95% CIs) of hip, knee, and hip/knee OA for those with high CVH were 0.71 (0.64, 0.79), 0.48 (0.44, 0.52), and 0.56 (0.52, 0.60), respectively. These associations were not modified by GRSs. In the joint association analyses, the lowest HR (hip OA: 0.48, 0.41–0.55; knee OA: 0.34, 0.30–0.39; hip/knee OA: 0.43, 0.39–0.47) of events were observed in those with both high CVH and low GRSs, compared to those low CVH and high GRSs.ConclusionOur findings underscore the importance of maintaining the maximum CVH to prevent the onset of OA, irrespective of genetic predisposition.